How to treat hypertension in Venlafaxine-medicated patients: pharmacokinetic considerations in prescribing Amlodipine and Ramipril - Augustin, Marc; Schoretsanitēs, Geōrgios; Gründer, Gerhard; Haen, Ekkehard; Paulzen, Michael (Journal of clinical psychopharmacology, 2018)
Background - Amlodipine (AMLO) and ramipril (RAMI) belong to the most prescribed drugs in patients with hypertension, a condition also encountered in depression. Venlafaxine may worsen hypertension because of noradrenergic properties. Although of special clinical relevance, data on pharmacokinetic interactions between AMLO, RAMI, and venlafaxine (VEN) are lacking. - Methods - Two TDM databases consisting of plasma concentrations of VEN and its active metabolite O-desmethylvenlafaxine (ODVEN) were analyzed. We considered a group of patients comedicated with AMLO, VAMLO (n = 22); a group comedicated with RAMI, VRAMI (n = 20); and a 4:1 control group age matched to the VAMLO group receiving VEN without confounding medications, V0 (n = 88). Plasma concentrations of VEN, ODVEN, and active moiety, AM (VEN + ODVEN); metabolic ratio (ODVEN/VEN); and dose-adjusted plasma concentrations (C/D) were compared using nonparametric tests. - Results - Groups did not differ in daily VEN dose, age, or sex. The metabolic ratio (ODVEN/VEN) was lower in the AMLO group (P = 0.029), whereas the RAMI group showed lower values for ODVEN (P = 0.029). All other parameters showed no significant differences. - Conclusions - Significantly lower values for the metabolic ratio in the AMLO group are unlikely to be explained by cytochrome P450 (CYP) 3A4 and weak CYP2D6 inhibition by AMLO. Other factors such as differences in CYP2D6 polymorphisms and metabolizer status may better explain the findings. Ramipril showed modest effects with changes in ODVEN concentrations that did not remain significant after dose-adjusted comparisons.